Glacial–Interglacial Cycles and Early Human Evolution in China - Zhenyu Qin; Xuefeng Sun (Land, 2023)
China is a crucial region for investigating the relationship between climate change and hominin evolution across diverse terrestrial ecosystems. With the continuous development of palaeoclimatology, chronology, and archaeology, the environmental and hominin record of the Early and Middle Pleistocene in China is steadily accumulating, shedding light on the effects of climate change on the distribution of early human settlements and population dynamics. However, the migration and dispersal of these early humans within long-term climate fluctuations and their underlying mechanisms remain to be clarified. Based on the spatial-temporal distribution of 95 Early to Middle Pleistocene archaeological sites in China, we found that intensified hominin activities gradually shifted southward under the influence of multiple glacial–interglacial cycles. The frequent bidirectional movements of these early humans between north and south were assumed as follows. During glacial periods, hominins living in North China migrated to southern areas, while inter-glacial periods witnessed the northward expansion of hominins inhabiting South China. Among all the potential driving mechanisms, we suggest that the available resources in terrestrial ecosystems may be the most fundamental factor. Combined with paleoenvironmental and archaeological records, we provide an Asian perspective for a better understanding of how the glacial–interglacial cycles shaped early human evolution.